Perancangan Mesin Pengolah Sampah Plastik Jenis Polyehthylene Terephthalate (PET) Menjadi Biji Plastik Dengan Metode Ekstrusi - Ihda Alwan, Muhammad; Eka Septiyani Arifin, Devi; Yuni Widiatmoko, Rudy (Journal of Applied Mechanical Engineering and Renewable Energy, 2025)
A plastic extrusion machine is a tool that can be used to process plastic waste into plastic pellets which can be reused to produce plastic products. Therefore, learning and applying these tools is useful for reprocessing plastic waste which is currently increasing. However, it is a shame that the tools currently on the market are relatively uneconomical for institutional scale processing, because the majority of tools on the market are intended for industrial scale. The output of this design produces a prototype tool with dimensions of 1005x350x830 mm and a capacity of 376 grams/hour. Maximum total energy consumption is less than 1 kW. The design of this plastic extrusion machine uses a screw conveyor, a 200Watt band heater and has 2 functions in 1 machine. The first function is to extrude chopped PET plastic and the second function is to cut the extrusion product so that the output of this machine is plastic pellets.